(untitled) (PUBMET, 2022)
Introduction. Several business models have emerged for open access (OA) monographs, and one of them is library crowdfunding (Collins, 2015; Speicher, 2018). Considering the importance of collaboration in OA (Deegan, 2017), it is no surprise that this model—which is based on libraries collaborating to fund the publishing of OA monographs—is considered innovative and possibly sustainable long-term (Leach-Murray, 2017). It encourages academic libraries to share the cost of publishing peer-reviewed OA monographs in various fields and take the burden of the author-pay model away from researchers (Reinsfelder, 2018). Well-known initiatives of this kind include Knowledge Unlatched (KU), Reveal Digital, and UnGlue.It (Bulock, 2018). Purpose. This study investigates how sustainable is this model and which factors besides those already known (i.e., budgeting, relevance of content, and the OA principle) can influence institutions to adopt it. The investigation relies on the innovation diffusion theory (Pinfield et al., 2021), since library crowdfunding for OA monographs brings innovation to how OA monograph publishing is funded. It also starts with a premise that a closer look at institutions that have already adopted the model can help identify the ‘early majority’ types of institutions. Methods. We traced the rankings of 124 European institutions that support or do not support the KU’s crowdfunding initiative for OA monographs from 2016 to 2020. The representative sample includes participating institutions from Western and Northern and largely non-participating Eastern European countries. The rankings were taken from THE World Rankings, Academic Ranking of World Universities, and QS World University in six categories: overall world ranking score, research output score, citation score, international outlook score, student size, and faculty size. By examining the characteristics of various types of ‘adopters’ identified by the innovation diffusion theory, we set out to answer two main research questions: 1) What types of institutions support library crowdfunding for OA monographs? and 2) How adopters and non-adopters rank in the world and what are their characteristics? Findings. Aside from institution’s budget, relevance of content, and belief in the tenets of the OA movement, the most reliable predictors for the crowdfunding model adoption include institution’s high world ranking, research output, citation impact, and international outlook. Student size and faculty size, in turn, are not as reliable predictors. Limitations. The Our study is limited to institutions ranked by all three sources and to the data of only one of the several existing crowdfunding initiatives for monographs. Future studies should expand to cover non-ranking institutions and other crowdfunding initiatives and explore various other types of innovations in the OA domain, as crowdfunding is but one of a number of approaches to financing OA publishing. Contribution. Despite its limitations, our study is the first to use the innovation diffusion theory and university ranking sources to profile institutions and to confirm the hypothesis that high-ranking institutions are the most likely to adopt library crowdfunding as their business model.